Music Student’s Approach to the Forced Use of Remote Performance Assessments - Ritchie, Laura; Sharpe, Benjamin T. (Frontiers in Psychology, 2021)
Music students at the University of Chichester Conservatoire completed questionnaires about their experience of the forced use of remote teaching and learning due to Lockdown, as imposed in the UK from March-June 2020, and how this impacted their self-beliefs, decision making processes, and methods of preparation for their performance assessments. Students had the choice to either have musical performance assessed in line with originally published deadlines (still in Lockdown) via self-recorded video or defer the assessment until the following academic year. Student’s choice to defer or submit the assessment during Lockdown was influenced by a range of forced factors, such as adaptions required by online teaching, limitations of rehearsal in their home environment, and the challenges in facilitating and recording their own assessments. Students completed online questionnaires about their self-efficacy, resilience, wellbeing, and provided free text responses explaining the reasoning for their decision to record their performance or to defer the assessment were coded to reveal patterns impacting their decision and preparation processes. Those choosing to submit their assessments demonstrated more strategies in their preparation and reported higher perceived self-efficacy scores. The specific conditions for this assessment, as a result of Lockdown, revealed correlations between resilience and both self-efficacy and wellbeing. The impact on teaching and the student experience is discussed and suggestions to support students in future settings of blended delivery are presented. Theoretical and practical implications are discussed.